DEVELOPMENT OF THE DERMATOPIA FLIPBOOK AS A LEARNING MEDIA FOR FACIAL CARE EDUCATION AMONG VOCATIONAL HIGH SCHOOL BEAUTY PROGRAM STUDENTS IN THE SPECIAL REGION OF YOGYAKARTA - Siti Shafira Uswatun Hasanah; Dr Ichda Chayati, M.P (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to develop a digital flipbook named Dermatopia as a learning medium for facial care among 11th-grade students in the Beauty and Skin Care Department at Vocational High Schools in the Special Region of Yogyakarta. The background of this research is the limitations of conventional learning media that are static, bulky, and less interactive, making it difficult for students to master the sequence of facial massage techniques independently in accordance with the Indonesian National Work Competency Standards (SKKNI) in the Beauty sector. This research employed a Research and Development (R&D) approach using the 4D model (Define, Design, Develop, Disseminate). The subjects were 75 eleventh-grade students from four vocational high schools in Yogyakarta. The instruments included material and media expert validation sheets, comprehension tests (pre-test and post-test), practice observation sheets, and student response questionnaires. Data were analyzed using descriptive qualitative and quantitative methods. The results showed that the Dermatopia flipbook has interactive characteristics that integrate anatomy of the skin, skin types, tools and cosmetic materials, and video tutorials on five basic and electric facial massage movements. Material expert validation obtained a score of 4.58 (98.75%) and media expert 4.51 (94.64%), indicating that the product is highly feasible. The effectiveness of the product was proven by an increase in the average student comprehension score from 67.80 to 86.40, a student response score of 4.60 (92%), and a practical accessibility rate of 92%. The flipbook can be accessed at https://buku-dermatopia.netlify.app/. It can be concluded that the Dermatopia flipbook is highly feasible and effective as a learning medium for facial care to support independent learning for Beauty Vocational High School students.